Low molecular weight heparin: a promising anticoagulant in pregnancy - Bangal, Vidyadhar B.; Giri, Purushottam A.; Chalasani, Shravani; Fernandes, Denita (International Journal Of Community Medicine And Public Health, 2017)
Venous thromboembolism (VTE) is a leading cause of maternal mortality and morbidity during pregnancy in developed countries. The incidence of VTE increases about 4-fold during pregnancy and at least 14-fold during the puerperium. Risk factors include a personal history of VTE, presence of inherited or acquired thrombophilia, a family history of VTE and general medical conditions, such as immobilisation, overweight, varicose veins, some haematological diseases and inflammatory disorders. VTE is considered potentially preventable with the prophylactic administration of anticoagulants. Low molecular weight heparin has emerged as choice of anticoagulant in the present day obstetric and infertility practice. It has many advantages over unfractionated heparin and warfarin. Longer duration of action, less frequent dosing schedule, better safety profile are few of the advantages. Higher cost as compared to warfarin and unfractionated heparin is the main limiting factor for its use.